Effect of endoscopic sinus surgery on general health related quality of life domains in chronic rhino sinusitis patients - Jose, Amal P.; George, Shibu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic rhino sinusitis (CRS) is a common health problem affecting around 5-12% of the general population in a year. Treatment of CRS consist of medical and surgical management. Surgical management is considered when patient is not responding to maximal medical treatment or in case of complication. Sino nasal outcome test 22 (SNOT- 22) is considered as the most appropriate instrument in the evaluation of HRQOL impairment in CRS patients. This study evaluated general health related quality of life (QOL) domains of SNOT- 22 changes following endoscopic sinus surgery. Methods: This study was conducted in 53 subjects who underwent endoscopic sinus surgery for chronic rhino sinusitis in Department of otorhinolaryngology, Government Medical College, Kottayam over a period of one year. Detailed history including SNOT-22 questionnaire enquired. Clinical, radiological and endoscopic examinations were performed. This patient followed up after 1 week, 1month and 3 months. SNOT-22 scores were recorded at each visit; data compiled and analysed with help of SPSS. Results: The baseline SNOT-22 score for study population was 37.51. General health related quality of life domains was assessed separately. The score for psychological dysfunction and sleep dysfunction decreased from 10.72, 6.00 to 1.58 and 1.02 respectively at the end of 3 months. Conclusions: Chronic rhinosinusitis patients reported significant improvement in psychosocial dysfunction and sleep related symptoms after endoscopic sinus surgery. Chronic rhino sinusitis patient with anxiety and depressive disorders need special attention to improve health related quality of life (HRQOL).